Preliminary investigation and application of a modified objects memory test in perioperative cognitive evaluation - Chen, Lanfeng; Gao, Baobin; Yan, Chaoyang; Wang, Zhengzheng; Bi, Yiqing; Chen, Hongfu; Jin, Haojie (Frontiers in Behavioral Neuroscience, 2023)
Objective To investigate the applicability of a modified verbal learning test redesigned from the memory subtest of the Syndrom Kurztest (SKT) in perioperative cognitive evaluation. Methods Patients receiving elective herniorrhaphy and their accompanying family members (set as normal controls), 55–75 years old, were randomly divided into two groups. The two groups received the self-made objects memory test derived from the SKT (SMOT) SMOT or a traditional auditory verbal learning test (AVLT). The cognitive evaluation was administered at the bedside on the day before surgery and the second day after surgery. Results The SMOT test was administered to 121 subjects, while 107 patients received the AVLT test. After confirming that there was no significant difference in cognitive function between patients and their family members, the results of the SMOT and AVLT tests were compared. The results showed that the “low-score” ratio of the SMOT was significantly lower than that of the AVLT test (P < 0.05), and the influencing factors of the SMOT were less than those of the AVLT test. However, the learning effect of the SMOT was more significant (P < 0.05). Conclusion This study preliminarily confirms that the SMOT has better applicability to elderly Chinese individuals than AVLT in perioperative cognitive evaluation, but its learning effect should be noted.